2007
DOI: 10.1001/archpedi.161.7.669
|View full text |Cite
|
Sign up to set email alerts
|

Child Care and the Well-being of Children

Abstract: Objective: To evaluate studies of child care with specific attention to the impact of age at entry and amount, quality, and type of care on children's adaptive functioning. Results: Children who began care early in life and were in care 30 or more hours a week were at increased risk for stress-related behavioral problems. Elevated risk was more likely if they had difficulties interacting with peers or had insensitive parents. Children in day care centers had higher language scores and early school achievement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 81 publications
(88 reference statements)
5
103
1
21
Order By: Relevance
“…This distinction is important because distinct patterns of childcare use may have different implications for child development. A significant proportion of children are receiving informal childcare arrangements, especially disadvantaged ones (Riley & Glass, 2002), and the effect of informal childcare is not well documented in the literature (Bradley & Vandell, 2007).…”
Section: Research Questionsmentioning
confidence: 99%
“…This distinction is important because distinct patterns of childcare use may have different implications for child development. A significant proportion of children are receiving informal childcare arrangements, especially disadvantaged ones (Riley & Glass, 2002), and the effect of informal childcare is not well documented in the literature (Bradley & Vandell, 2007).…”
Section: Research Questionsmentioning
confidence: 99%
“…A frequência a creches de crianças em condições socioeconômicas menos favorecidas pode ser considerada uma das estratégias dos países subdesenvolvidos para estimular o crescimento e desenvolvimento infantil. Tal fato é explicado por serem insatisfatórias as condições de moradia e de cuidado com os lactentes nessas populações urbanas empobrecidas (8)(9)(10)(11)(12) . A avaliação do estado nutricional da população infantil é essencial para que seja conferida a evolução das condições de saúde e de vida, considerando sua influência decisiva sobre os riscos de morbimortalidade, crescimento e desenvolvimento infantil, além de possibilitar intervenções precoces e melhorar a qualidade de vida da população de forma geral (6,13,14) .…”
Section: Introductionunclassified
“…Importantly, the early aggression identified in some studies did not lead to later aggressive criminal acts (15). Although there may be some negative behavioural effects of long-term nonparental child care, children may gain social skills including peer play, selfconfidence and managing new situations (17). In a review (15) of nine studies conducted between 1975 and 1990, some found that boys in daycare were more aggressive, others found no difference and some found that girls were more aggressive.…”
Section: Behaviour and Developmental Outcomes Of Child Care Centresmentioning
confidence: 99%
“…There may be an association between the time in nonparental care and poor peer interactions and adjustment problems (17). Some small studies (19) have suggested that children enrolled in full-time child care early in life are at an increased risk of attachment insecurity.…”
Section: Behaviour and Developmental Outcomes Of Child Care Centresmentioning
confidence: 99%
See 1 more Smart Citation